FORMATION AND DEVELOPMENT OF NORMAL-FAULT CALDERAS AND THE INITIATION OF LARGE EXPLOSIVE ERUPTIONS - Gudmundsson A. (My University, 1998)
The ring fractures that form most collapse calderas are steeply inward-dipping shear fractures, i.e., normal faults. At the surface of the volcano within which the caldera fault forms, the tensile and shear stresses that generate the normal-fault caldera must peak at a certain radial distance from the surface point above the center of the source magma chamber of the volcano. Numerical results indicate that normal-fault calderas may initiate as a result of doming of an area containing a shallow sill-like magma chamber, provided that the area of doming is much larger than the cross-sectional area of the chamber and that the internal excess pressure in the chamber is smaller than that responsible for doming. This model is supported by the observation that many caldera collapses are preceded by a long period of doming over an area much larger than that of the subsequently formed caldera. When the caldera fault does not slip, eruptions from calderas are normally small. Nearly all large explosive eruptions, however, are associated with slip on caldera faults. During dip slip on, and doming of, a normal-fault caldera, the vertical stress on part of the underlying chamber suddenly decreases. This may lead to explosive bubble growth in this part of the magma chamber, provided its magma is gas rich. This bubble growth can generate an excess fluid pressure that is sufficiently high to drive a large fraction of the magma out of the chamber during an explosive eruption.
Keywords: COLLAPSE CALDERAS; EXPLOSIVE ERUPTIONS; RING FAULTS; FAULT SLIP